Cumulative creep damage for unidirectional composites under step loading - Rui Miranda Guedes (2012)
The creep lifetime prediction of unidirectional composite materials under step loading, based on constant loading durability diagram, is analyzed for the two-step creep loading condition. For this purpose different nonlinear cumulative-damage laws are revisited and applied to predict creep lifetime. One possible approach to accounting for damage accumulation is provided by the continuum-damage mechanics (CDM). However, the CDM lifetime expression obtained for constant loading condition presents some drawbacks. Specifically, the upper stress range is not accommodated by CDM form. A modification of CDM is proposed, forcing the CDM to capture the short-term creep failure. It is proven that this modified CDM (MCDM) does not yield the same predictions as the Linear Cumulative-damage law (Miner's law). Predictions obtained from the nonlinear cumulative-damage laws are compared against synthetic lifetime generated by a micromechanical model that simulates unidirectional composites under two-step creep loading condition. Comparable deviations from Miner's law are obtained by the nonlinear cumulative-damage laws.